STRATEGI KOMISI PEMILIHAN UMUM KABUPATEN KAMPAR DALAM MENINGKATKAN PARTISIPASI PEMILIH PADA PEMILIHAN BUPATI KAMPAR TAHUN 2017 - Mas Anizan; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is motivated by the regional head election held simultaneously for the first time in Kampar regency. The election of Kampar district head was also appointed as the Pilkada Pilot project of National 2017 by the Central Election Commission with the target of voter participation which was set at 77%. In the implementation, the voter participation rate is only able to reach 66% increase from the previous Bupati election but not reach the desired target as the National Pilot project. Nevertheless, the selection of Kampar Regent can be said to be successful in its implementation. This study aims to determine the strategy of Kampar General Election Commissions in increasing voter participation in elections of Kampar Regent 2017 and to know the supporting factors and obstacles of Kampar General Election Commissions strategy in increasing voter participation in elections of Kampar Regent 2017. Theories used are strategy theory, political participation theory and theory of political socialization. Research Methods used in the writing of this thesis is Qualitative. Data type in this research is primary data and secondary data. Data collection techniques in this study are interviews and documentation. Data analysis technique used is descriptive qualitative.The results of this study indicate that the General Election Commissions strategy enhances voter participation through: (1). Strengthening Strategy, the effort is to improve the capacity and quality of election organizer of Kampar Regent through technical guidance and improve communication and information disclosure through information board, mass media, through stakeholder, mosque and smart house election. (2). Strategy Rationalization, the effort is to socialize face to face communication. 3). Strategy for Persuasion, conducting relaxed walking program, roadshow, establishment of balimau kasai booth and conducting interactive dialogue both through television and radio. (4). Confrontation Strategy, in the form of socialization of choosing and disadvantage if not vote, then the General Election Commissions invites the community to choose through khutbah in mosque with theme of choosing leader. Factors supporting the implementation of Kampar General Election Commissions strategy are the availability of adequate human resources, professionalism, support from the government and Stakeholder.Keywords: Strategy General Election Commission Improving Participation